2015
DOI: 10.1039/c5bm00307e
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer assemblies for antibacterial applications

Abstract: The adhesion and proliferation of bacteria on various artificial surfaces affects the functionality of these specific interfaces. To overcome the problems caused by bacterial growth on these surfaces, various antibacterial coatings were developed. In this review, we summarized most of the antibacterial surfaces prepared by the Layer-by-Layer (LbL) assembly approach and classified these LbL films based on their antibacterial mechanisms. In the first group, the bactericidal LbL assemblies which incorporate vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
121
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 100 publications
(174 reference statements)
0
121
0
3
Order By: Relevance
“…Theo báo cáo, quá trình chế tạo màng bọc này được tiếp cận theo hai hướng [2]. Hướng thứ nhất được các nhà khoa học quan tâm là chế tạo các màng đa lớp có chứa các biocide khác nhau, các biocide này hoặc là liên kết chặt chẽ với bề mặt vật liệu -qua đó bảo vệ bề mặt khỏi vi khuẩn, hoặc là có khả năng kháng vi sinh vật, tự phân hủy sinh học và đảo thải ra ngoài môi trường.…”
Section: đặT Vấn đềunclassified
See 1 more Smart Citation
“…Theo báo cáo, quá trình chế tạo màng bọc này được tiếp cận theo hai hướng [2]. Hướng thứ nhất được các nhà khoa học quan tâm là chế tạo các màng đa lớp có chứa các biocide khác nhau, các biocide này hoặc là liên kết chặt chẽ với bề mặt vật liệu -qua đó bảo vệ bề mặt khỏi vi khuẩn, hoặc là có khả năng kháng vi sinh vật, tự phân hủy sinh học và đảo thải ra ngoài môi trường.…”
Section: đặT Vấn đềunclassified
“…Để thực hiện chức năng bảo vệ bề mặt khỏi sự phá hủy sinh học, các biocide được hoạt hóa dưới dạng các polycation (hydrochloride polyallylamine, polyvinylamine, hydrochloride polydiallyldimethylammonium, polyethyleneimine, chitosan), qua đó chúng (biocide) được tiếp nhận điện tích dương. Khi tiếp xúc với bề mặt này, các vi khuẩn bị tiêu diệt [2] do tác động của chúng với các màng tế bào, đồng thời tạo ra sự phân chia, kết dính nhờ đó kích thích quá trình hấp thụ vi sinh vật lên bề mặt màng. Tác dụng kháng khuẩn của các màng bọc này kéo dài so hơn với các màng -mà tại đó biocide được thải ra môi trường ngoài.…”
Section: đặT Vấn đềunclassified
“…68 In general, the antibacterial materials should be able to kill bacteria or prevent bacterial adhesion or both. 69 Bactericidal polymers are the most straightforward solution to bacterial adhesion and growth. Thus, extensive e®orts have been made to develop bactericidal polymers for antibacterial applications.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…However, the concern with these multifunctional polymeric assemblies are the doubled or tripled complexity of the polymeric system and the di±-culty to scale up synthesis for real applications. 69 In short, we have summarized the strategies or routes to design antibacterial polymeric assemblies based on reported approaches. Most of the studies mentioned in this review reported promising antibacterial e®ects.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…Coating by LBL is an advanced technique to assemble polyelectrolyte multilayer (PEM) films onto polymer surfaces, mesoporous silica nanoparticles and Ti surfaces by sequential adsorption of oppositely charged polyanions and polycations via electrostatic interactions [16][17][18][19][20][21][22]. This technique is expected to provide a more durable coating due to the electrostatic attractions between layers and between the first layer and substrate [6].…”
mentioning
confidence: 99%